Clinical significance of lower respiratory tract culture within 48 h of admission in patients with viral pneumonia: an observational study - Chen, Lu-Lu; Weng, Heng (BMC pulmonary medicine, 2024)
Background The aim of this retrospective study was to examine the risk factors of positive lower respiratory tract cultures and to investigate whether nosocomial infections are common in patients with positive lower respiratory tract cultures. Methods We enrolled 86 patients diagnosed with influenza A-related critical illness who were treated at Fuzhou Pulmonary Hospital of Fujian in China between 1st October 2013 and 31st March 2019. The of admission were used to divide the enrolled patients into two groups. Sputum and bronchoalveolar lavage fluid specimens were collected within 48 h after admission for culture. All samples were cultured immediately after sampling. Nosocomial infections are defined as any symptom or sign of pulmonary infiltration, confirmed by X-ray, after 5 days of admission and positive results from one or more cultures. Results The average age of this cohort was (54.13 ± 16.52) years. Based on the culture results, Staphylococcus aureus and Candida albicans had the highest positive rates (3.40% (3/86) and 20.90% (18/86), respectively). In patients with positive lower respiratory tract cultures, the incidence of nosocomial infection was 73.30% (22/30) five days after admission. However, the incidence of nosocomial infection was lower (42.80%, 24/56) in patients with negative lower respiratory tract cultures. Hemoptysis, systolic pressure at admission, and blood urea nitrogen level at admission were all independent risk factors for positive lower respiratory tract cultures within 48 h of admission. Conclusion Our data showed that a significant proportion of patients with pneumonia exhibited co-infections with bacteria or fungi within five days of hospital admission. Hemoptysis, systolic pressure, and blood urea nitrogen levels at admission emerged as the key risk factors. These findings underscore the necessity of closely monitoring patients with influenza infection, particularly for positive bacterial or fungal cultures within the initial 48 h of admission.